2007
DOI: 10.1007/s11224-007-9209-3
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the interactions between N, N-dimethylformamide and aromatic hydrocarbons

Abstract: The B3LYP and MP2 methods with 6-31G* basis set were used to predict the geometries of N, N-dimethylformamide (DMF) dimer and DMF-aromatic hydrocarbons interaction systems. A total of 10 conformers were obtained with no imaginary frequencies, respectively. The interaction energies of these binary mixtures have been obtained. The analyses of chelpg charge distribution and the atoms in molecules theory (AIM) were used to analyze the nature of the interaction. The results show the presence of hydrogen bonds betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Apparently, neither the charge transfer of configuration a nor that of configuration b has any relation to the binding energy that increases with the introduction of chlorine. The result shows that the amount of transferred charge seems not to correlate with any interaction energy term [33,34], which means they are not the charge-transfer complexes as mentioned in the literature [16].…”
Section: Charge Transfer and Charge Populationmentioning
confidence: 72%
“…Apparently, neither the charge transfer of configuration a nor that of configuration b has any relation to the binding energy that increases with the introduction of chlorine. The result shows that the amount of transferred charge seems not to correlate with any interaction energy term [33,34], which means they are not the charge-transfer complexes as mentioned in the literature [16].…”
Section: Charge Transfer and Charge Populationmentioning
confidence: 72%
“…In the next article, by Shan et al [340], theoretical calculations were used to predict the geometries of N,Ndimethylformamide (DMF) dimer and DMF-aromatic hydrocarbons interaction systems. It is concluded that the hydrogen bonding interaction plays an important role in the DMF dimer and the DMF-aromatic hydrocarbon complexes.…”
Section: Issuementioning
confidence: 99%
“…Qingyu Ge et al [15] have investigated the hydrogen-bonding interaction of DMF-chloromethane binary system with density functional (DFT) method at 6-311++G** basis set level. The complex formed between DMF and aromatic hydrocarbon (C 6 H 6 , C 6 H 5 CH 3 , C 6 H 5 CN) was also investigated with ab initio method at MP2/6-31G* level, which revealed that the hydrogenbonding interaction plays an important role in these systems [16].…”
Section: Introductionmentioning
confidence: 99%